Aktivitas Antimikroba Ekstrak Dietil Eter Rimpang Lempuyang Wangi (Zingiber aromaticum Vahl.) Terhadap Bakteri Patogen Secara Klt-Bioautografi - Zaraswati Dwyana (Jurnal Ilmu Alam dan Lingkungan, 2017)
Antimicrobial Activity of Dietil Eter extract of Lempuyang Wangi Rimpang (Zingiber aromaticum Vahl.) to pathogen bacterial  through TLC-Bioautography. Research has done by screening test using Streptococcus mutans, Vibrio sp, Pseudomonas aeruginosa, Bacillus subtilis, Staphylococcus epidermidis, Staphylococcus aureus, Salmonella typhi, Escherichia coli and Candida albicans by methanol extract, diethyl ether extract and nbuthanol extract which were use 1 mg/ml. Result which obtained exhibit diethyl ether extract inhibit the growth of Bacillus subtilis, Salmonella typhi, Staphylococcus epidermidis, and Vibrio sp. Antimicrobial potential assay of diethyl ether extract of Zingiber aromaticum Vahl. has done by liquid dilution method to get the MIC value in concentration of 0,05 %, 0,1 %, 0,2 %, 0,4%, and 0,8 % which continued by smearing on solidified medium to get the MLC value. The result shown that MKC could not be determined due to turbidity of the test solution mean while the MLC of the extract as much as 0,2 % on Bacillus subtilis and Salmonella typhi and  0,4 % on Staphylococcus epidermidis and Vibrio sp. TLC-bioautography test has done to get the compound which had antimicrobial activity. The best result was obtained from separation through TLCbioautography by means of eluent n-hexan : ethyl acetate (8 : 2). TLC-bioautography test result shown that the spot in Rf 0,07 has antimicrobial activity on Staphylococcus epidermidis, Rf 0,2 has antimicrobial activity on Vibrio sp., Rf 0,07, 0,45, 0,56 and 0,69 has antimicrobial activity on Bacillus subtilis, and Rf 0,2 has antimicrobial activity on Salmonella typhi. Identification result of the chemical component shown that the active compound which given positif result on spot viewer were in Rf 0,07; 0,2; 0,45; 0,56; and 0,69.